Farmer participation in bean research in Africa: experiences from the field - David, S. (International Center for Tropical Agriculture, 1995)
This paper defines basic tenents of the participatory research approach in the context of agricultural technology development. It reviews CIAT`s experiences in Eastern Africa with involving farmers in bean research at three levels; research planning and implementation, varietal selection and seed multiplication. The role farmers can play in evaluating the impact of new bean technologies is briefly assessed.